2023
DOI: 10.32604/cmc.2023.028631
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Neural Network Based Speech Emotion Recognition for燬mart燗ssistance

Abstract: Day by day, biometric-based systems play a vital role in our daily lives. This paper proposed an intelligent assistant intended to identify emotions via voice message. A biometric system has been developed to detect human emotions based on voice recognition and control a few electronic peripherals for alert actions. This proposed smart assistant aims to provide a support to the people through buzzer and light emitting diodes (LED) alert signals and it also keep track of the places like households, hospitals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Research such as [20] specified that this type of method will facilitate the creation of voicecontrolled systems, fulfilling the essential requirements of human beings and taking into account the possible scenarios of human-machine collaboration, achieving a significant improvement. Also, Kumar et al [35] described that the proposed algorithms offer better performance during their operation than existing technologies, suggesting the support vector machine algorithm. The authors in [36] discussed and recommended using seizure model-centered machine learning algorithms for action recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Research such as [20] specified that this type of method will facilitate the creation of voicecontrolled systems, fulfilling the essential requirements of human beings and taking into account the possible scenarios of human-machine collaboration, achieving a significant improvement. Also, Kumar et al [35] described that the proposed algorithms offer better performance during their operation than existing technologies, suggesting the support vector machine algorithm. The authors in [36] discussed and recommended using seizure model-centered machine learning algorithms for action recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Many of these features are categorized further based on numerous emotional factors. In particular, their study demonstrates that deep RNNs outperform conventional ML algorithms when identifying emotions in music based on instrument categories, which is a key finding in the relevant literature.The need to give piano students a way to evaluate their playing performance is highlighted, so they can get helpful feedback [24][25][26][27] . The realtime recognition of single notes and the non-real-time recognition of multiple notes are both handled by this method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The deep neural network is a subfield of AI and directly learns features from the data before making decisions. In numerous fields, including speech recognition [27][28][29][30], image processing [31][32][33][34], natural language processing [35,36], and bioengineering [37], deep learning algorithms have demonstrated that they are the most effective and exceptional machine learning algorithms. Additionally, several studies demonstrated that deep learning algorithms outperform traditional machine learning methods when applied to various complex learning problems [38,39].…”
Section: Deep Neural Networkmentioning
confidence: 99%